IDENTIFIKASI NILAI EKONOMI EKOSISTEM HUTAN MANGROVE DI DESA TAWIRI, AMBON - Sarah Hiariey, Lilian (Jurnal Organisasi Dan Manajemen, 2009)
The ecological role of mangrove ecosystem is, economically, socially and physically, highly significant. Despite the many benefits provided by mangroves, they tend to be under intense pressure from competing resource used by local villagers, in particular, as firewood, or charcoal. The ecosystem is typically crucial, hence the benefits and values need to identify and estimate economically. The objectives of this research are: (1) to identify economic values of mangroves based on ecosystem benefits; and (2) to estimate total economic value (TEV) of use-value and non-use value of mangroves. The method of economic valuation was applied to estimate TEV based on the benefits of mangroves ecosystem (direct-use value, indirect-use, option use, and existence use values). Results of this research are as follows. (1) Functions and benefits of the mangrove ecosystem in the Village of Tawiri consisted of direct-use (fuel wood collection for the subsistence needs of local villagers, wild animals used by humans for subsistence purposes, near by fishing activities); indirect-use (natural barrier to shoreline erosion, highly nutritious food source for animals in the mangrove area), option use (biodiversity benefits), and existence use (WTP). (2) The TEV of mangrove was Rp 24,887,887 per year, consisting of direct-use value of Rp 11,299,500 per year (45.40%), indirect-value of Rp 9,098,077 per year (36.56%), existence value of Rp 4,083.750 per year (16.41%) and option value of Rp 406,560 per year (1.63%).